2018
DOI: 10.1016/j.bone.2017.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid metabolism by the osteoblast

Abstract: The emergence of bone as an endocrine organ able to influence whole body metabolism, together with comorbid epidemics of obesity, diabetes, and osteoporosis, have prompted a renewed interest in the intermediary metabolism of the osteoblast. To date, most studies have focused on the utilization of glucose by this specialized cell, but the oxidation of fatty acids results in a larger energy yield. Osteoblasts express the requisite receptors and catabolic enzymes to take up and then metabolize fatty acids, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 92 publications
4
53
0
Order By: Relevance
“…MAT, derived from the differentiation of mesenchymal stem cells (MSC) into adipocytes, increases in bonefragility states; however, its potential role in promoting bone formation and/or resorption has not been elucidated, despite active investigation. Moreover, fatty acid β-oxidation markers rise in bone in the setting of exercise, concomitant with increased bone quantity; this along with research (9,20) demonstrating the reliance of the osteoblast on β-oxidation support MAT's role as an energy depot. (16)(17)(18) Recent work established MAT to be suppressed by exercise, in rodents (16,18) and humans, (19) suggesting that MAT may function similarly to white adipose tissue in a calorie-replete state as an energy depot.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…MAT, derived from the differentiation of mesenchymal stem cells (MSC) into adipocytes, increases in bonefragility states; however, its potential role in promoting bone formation and/or resorption has not been elucidated, despite active investigation. Moreover, fatty acid β-oxidation markers rise in bone in the setting of exercise, concomitant with increased bone quantity; this along with research (9,20) demonstrating the reliance of the osteoblast on β-oxidation support MAT's role as an energy depot. (16)(17)(18) Recent work established MAT to be suppressed by exercise, in rodents (16,18) and humans, (19) suggesting that MAT may function similarly to white adipose tissue in a calorie-replete state as an energy depot.…”
Section: Introductionmentioning
confidence: 84%
“…(16)(17)(18) Recent work established MAT to be suppressed by exercise, in rodents (16,18) and humans, (19) suggesting that MAT may function similarly to white adipose tissue in a calorie-replete state as an energy depot. Moreover, fatty acid β-oxidation markers rise in bone in the setting of exercise, concomitant with increased bone quantity; this along with research (9,20) demonstrating the reliance of the osteoblast on β-oxidation support MAT's role as an energy depot.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…It already had been reported that HPdLF show a distinct osteogenic differentiation potential 31 , 32 , 56 , which can be stimulated by several external cues 35 , 57 59 . In addition, fatty acids can affect the differentiation of osteoblasts 60 . However, how they influence HPdLF was unknown so far.…”
Section: Discussionmentioning
confidence: 99%
“…Such a change presents multiple advantages for bone. Firstly, the reduction in insulin action would increase blood glucose, a fundamental substrate for bone formation [36] particularly in early osteoblasts [31] rather than later, when free fatty acids may be more important [37] . This bias in glucose utilisation toward early osteoblasts is consistent with the ability of NPY/Y1 receptors to regulate glucose homeostasis through osteoglycin release also being restricted to early, not late osteoblasts [7] , and suggests that osteoblast-mediated regulation of osteoglycin occurs in early osteoblasts, in line with its peak expression at this stage of differentiation [38] .…”
Section: Discussionmentioning
confidence: 99%